2020
DOI: 10.1177/0306624x20904704
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of EEG-Neurofeedback on the Modulation of Impulsivity in a Sample of Cocaine and Heroin Long-Term Abstinent Inmates: A Pilot Study

Abstract: The aim of this pilot study was to assess whether neurofeedback (NFB) can be useful in the treatment of impulsive behavior in long-term abstinent cocaine and heroin addicts. A single-blind sham-controlled NFB protocol was carried out to assess the effects of NFB on impulsivity in 20 (10 + 10) cocaine and heroin long-term abstinent addicts ( Diagnostic and Statistical Manual of Mental Disorders [4th ed., text rev.; DSM-IV-TR]). Psychotic and neurologic diseases were excluded. Participants underwent 40 NFB sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 95 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…In three unmedicated patients, 20 sessions of training decreased the clinical estimates of depression (MADRS and HAM-D) and excessive frontal and central theta and alpha powers. In a group of drug addicts sentenced for robbery, some specific improvement on HAM-D score was shown after infralow-frequency (0.01-0.02 MHz) neurofeedback with a concurrent suppression of a number of bands in the 1-40 Hz range [135]; however, this study remains the only one in this submodality dealing with depression estimates.…”
Section: 3mentioning
confidence: 66%
“…In three unmedicated patients, 20 sessions of training decreased the clinical estimates of depression (MADRS and HAM-D) and excessive frontal and central theta and alpha powers. In a group of drug addicts sentenced for robbery, some specific improvement on HAM-D score was shown after infralow-frequency (0.01-0.02 MHz) neurofeedback with a concurrent suppression of a number of bands in the 1-40 Hz range [135]; however, this study remains the only one in this submodality dealing with depression estimates.…”
Section: 3mentioning
confidence: 66%
“…After ILF-Neurofeedback training, clinical symptoms, such as depressive symptoms, anxiety, impulsivity and attention, had improved and the benefits were higher than in the control group. The authors suggested that Infra-low Neurofeedback was better than placebo in the modulation of impulsivity in the examined population (Corominas-Roso et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…7 Among various mental disorders, research on the effects of neurofeedback in relation to addiction also continues to advance. 8 Specifically, neurofeedback protocols based on brainwave assessments have primarily focused on substance use disorders. EEG-based neurofeedback has shown promising outcomes in alcohol use disorder by reducing impulsivity, recklessness, and risk aversion, and in nicotine addiction by decreasing smoking rates and cravings.…”
Section: Introductionmentioning
confidence: 99%